Ruthenium mimics of [Fe]-hydrogenase: synthesis, reactivity and peptide conjugation - Wong, Zhen Xuan (Nanyang Technological University, 2023)
In this work, further derivatization on the aminopyridyl ring at the 4- or 6-position of the previously reported ruthenium-based structural mimics of the [Fe]-hydrogenase was explored to assess their structural and electronic effects. It was found that there is a substituent effect at the 6-position on whether isomers may be observed for these complexes. The sixth coordination site on the metal centre, trans to the carbamoyl moiety, was also shown to be labile via experimental and Density Functional Theory (DFT) computational studies, consistent with known chemistry of the native [Fe]-hydrogenase. Reactivity studies using models of amino acids, protected amino acids and peptides, suggest that complexation is specific for the thiol functionality, corroborating earlier work that the complex binds to the cysteine active site of papain. Conjugation onto decapeptides which mimic the active site of papain was also successfully achieved. While the ruthenium complexes were found to be excellent catalysts for organosilane hydrolysis, especially for primary silanes, their peptide conjugates on the other hand showed no catalytic activity, suggesting that selectivity may be achieved via tuning of the steric bulk of the aminopyridyl substituents or the thiolate ligand or peptide.